KARAKTERISTIK FISIK RUMAH TINGGI SUWAWA DAN RUMAH BELE LI TAUDA’A DI PROVINSI GORONTALO - Rahmawati Eka; Umar Umar (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
The purpose of this research is to identify the physical characteristics of the Suwawa High House and the Bele Li Tauda'a House. The research method uses descriptive qualitative with locations in Kab. Bone Bolango and Gorontalo District. Field surveys were carried out in April – May 2023, starting with initial data collection followed by semi-structured interviews, field observations then data structuring, as well as confirmation of data with realities on the ground and the views of traditional leaders. The results showed that the physical characteristics of both were the same on the roof, the top part was triangular in shape with a second layer in the middle of the roof of the building.